Thyroidectomy for differentiated carcinoma in older patients on ashort stay basis - Del Rio, P.; Sommaruga, L.; Berzer, et al., L. (Acta Biomedica Atenei Parmensis, 2009)
Background: Total thyroidectomy is the treatment of choice for thyroid cancer and for selected benign thyroid conditions. The aging of the general population and the improvements in surgical technique induced an extension of the surgical indications to major thyroid surgery to older patients also on a short stay basis. Methods: From January 2004 to December 2006, 152 patients affected by thyroid carcinoma underwent total thyroidectomy on a short stay basis. We divided our series in 2 groups of patients according to the age (> or < of 65 yrs) and considered the outcome analysing several factors including: ASA score, mean operative time, mean hospital stay, tumour size, and post-operative complications. Results: The groups consisted of: 115 pts with a mean age of 46,81±11,63 years and 37 pts with a mean age of 74,53±3,71 years for the younger and older group respectively. The differences in ASA score and hospital stay were statistically significant between the groups (P< 0.007 and P< 0.004); neither postoperative haemorrage nor permanent hypocalcemia was observed. One permanent paralysis of the recurrent laryngeal nerve was noted at 12 months follow up; transient hypocalcemia, which resolved in all cases within 30 days from surgery, was reported in 23 and in 7 patients in the younger and older group respectively. Conclusions: Although a longer length of stay was noted in the older group and possibly related to a higher ASA score and a worse preoperative airways condition, total thyroidectomy for differentiated thyroid carcinoma may be safely carried out in older patients on a short stay basis if performed by an expert staff and in the setting of a multidisciplinary and exhaustive preoperative assessment.